A novel approach to secret data concealment with high cover text capacity and security. (15th November 2019) - Azeem, Muhammad; He, Jingsha; Ditta, Allah; Akhtar, Faheem; Daudpota, Sher Muhammad
Massive technological advancement and rapid internet growth has made the security of secret data more challenging for security researchers. Though, steganography techniques were also evolved but still require large cover text to conceal large message. Therefore, to deal capacity issue, present research articulates a novel approach to achieve high data concealment capacity of cover text along with security by using combination of steganography and cryptography. Current algorithm applies four-layer encryption on secret message and seven Unicode characters such as invisible plus (IP), invisible separator (IS), inhabit symmetric swapping (ISS), left to right override (LRO), (ZWNJ), zero width joiner (ZWJ), zero width non-joiner and zero width character (ZWC), are employed to embed secret information into English carrier text to generate stego text object. The result reflects tremendous increase of 300% in carrier text capacity and encryption significantly enhances the security of secret information. Moreover, the identical carrier and stego text reduces hacker's attention.